Factors affecting Consumers Satisfaction towards Advertising Media: A Comparative Study between Traditional Advertising and Online Advertising in Malaysia - Idris, Azni; Haque, A. K. M. Ahasanul; Ab. Yajid, Mohd Shukri; Khatibi, Ali (2009)
Advertising plays an important role in daily life. It is able to generate sales and brand recall towards certain products and services. By understanding consumers’ attitude towards advertising, designers and marketers can better strategize their advertising designs. A better understanding of interactivity can also help to improve the effectiveness of interactive media such as the internet. These attitudinal relations should play an essential role in consumer’s decisions on which media to choose based on the benefits that the media provide.